ANALISIS PENGARUH PEMASANGAN CONTROLLED MODULUS COLUMN (CMC) PADA DAYA DUKUNG DAN PENURUNAN TANAH LUNAK - Julita Hayati; Alfredo, Alexander; Sitepu, Arif Rahman Hakim; Syuhada, Syahidus (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
The construction of a structure on soft soil has the potential for structural failure. This phenomenon occurs because the low bearing capacity of soft soil is accompanied by high compressibility, resulting in large settlements and low stability. This problem needs to be solved by soil improvement. In the Indrapura–Kisaran STA 112 + 500 Toll Road Construction Project, soil will be filled more than the ground's bearing capacity. Therefore, a soil improvement method using a Controlled Modulus Column (CMC) is necessary. The analysis method used in this study uses analytical methods and the finite element method (FEM). The analysis was performed by comparing the bearing capacity and settlement in conditions without improvement (preloading) and with improvement using CMC. The installation of CMC with a spacing of 1 meter, a diameter of 0.42 meters, an LTP thickness of 1 meter, and a concrete quality of 16.41 MPa showed an increase in soil bearing capacity of 30%. The rise in ground bearing capacity also affected soil compressibility, resulting in a reduction of up to 68% in soil settlement. Therefore, installing CMC on soft soil effectively increases bearing capacity and reduces settlement. Ground stability is improved, with the safety factor rising to 2.11. Keyword: bearing capacity, Controlled Modulus Column (CMC), settlement, soft soil, soil improvement